The Influence of Learning Styles and Kolb Preferences on Training Effectiveness at the Learning and Behavior Level (Kirkpatrick Model): a Study at PT. Revass Utama Medika - Abdul Fattah; Arief Bimantoro Suharko (Sean Institute, 2025)
This study aims to analyze the influence of Kolb's learning style on the effectiveness of Customer Management training for employees of the Sales Division of PT. Revass Utama Medika, as measured through two levels of Kirkpatrick evaluation, namely Level 2 (learning) and Level 3 (behavior), and considering the role of learning preferences as a moderating variable. This study used a total population sampling method on 58 respondents, all of whom were training participants. Data collection was conducted one week after the online training, using a Likert-scale questionnaire instrument. Data analysis was carried out using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method. The results showed that Kolb's learning style had a positive and significant effect on material understanding (Level 2) with a p value <0.05, but did not have a significant effect on changes in work behavior (Level 3). Conversely, learning preferences had a positive and significant effect on changes in work behavior (p <0.05). The moderating effect of learning preferences on the relationship between learning styles and work behavior was not significant (p > 0.05). These findings indicate that matching training methods to individual preferences contributes to the application of training outcomes in the workplace, while learning styles play a greater role in shaping understanding of the material. This study provides theoretical contributions by integrating Kolb's learning style model and Kirkpatrick's training evaluation into a single analytical framework, as well as practical contributions to human resource management in designing training that adapts to employee learning styles.